AI in Content Evolution: Transforming Digital Landscape - Ankur Tiwari (Jurnal Komputer, Informasi dan Teknologi, 2022)
The rapid advancements in AI (Artificial Intelligence) have transformed the definition and utilization of digital content, revealing it to be an activity beyond mere creating and sharing digital content. From robot journalism and individualised advertising to tailored content recommendation AIs, artificial intelligence has emerged as the preeminent engine behind digital innovation. In this paper we present a survey of how content production workflows, user engagement and creativity itself have been transformed by new tools and technologies encompassing the Natural Language Processing (NLP) / Machine Learning field with recent advances in generative models. It also considers the ethical implications of AI-generated content in key areas such as authenticity, intellectual property and algorithmic bias. By examining opportunities and challenges, the work underscores the centrality of AI in democratizing content creation and promoting dynamic human–machine collaboration. The paper finally contends for a paradigm shift from static digital media to an adaptive, data-based and interactive ecosystem that constantly learns and reacts to the explicit and implicit audience activity during content evolution thanks to AI.